Deep neck space infection in the paediatric age group – a review - Swain, Santosh Kumar; Sahana, Ranita (Pediatria Polska - Polish Journal of Paediatrics, 2020)
Deep neck space infection (DNSI) is a rare clinical entity in the paediatric age group. However, it can cause significant morbidity and mortality in children. It has insidious presentations but can lead to a fatal and rapid course, which warrants careful observation by the clinician. Common causes of DNSIs are odontogenic and pharyngotonsillar infections. Children with DNSI may present with fever, neck swelling, and breathing difficulty. The fatal complications of DNSI in children are airway obstruction, mediastinitis, internal jugular vein thrombosis, pneumonia, and meningitis. The diagnosis of the DNSI is often challenging to the paediatrician or otolaryngologist. The three important things for successful treatment of the DNSI are antibiotic therapy, surgical drainage, and protection of the airway. Because of the complex anatomy of the neck, the airway management and surgical treatment may be challenging. The aim of this review article is to describe details of aetiopathology, clinical presentation, investigations, and current treatment.